Sustained release biodegradable solid lipid microparticles: Formulation, evaluation and statistical optimization by response surface methodology - Hanif Muhammad; Khan Hafeez Ullah; Afzal Samina; Mahmood Asif; Maheen Safirah; Afzal Khurram; Iqbal Nabila; Andleeb Mehwish; Abbas Nazar (Acta Pharmaceutica)
For preparing nebivolol loaded solid lipid microparticles (SLMs) by the solvent evaporation microencapsulation process from carnauba wax and glyceryl monostearate, central composite design was used to study the impact of independent variables on yield (Y1), entrapment efficiency (Y2) and drug release (Y3). SLMs having a 10-40 μm size range, with good rheological behavior and spherical smooth surfaces, were produced. Fourier transform infrared spectroscopy, differential scanning calorimetry and X-ray diffractometry pointed to compatibility between formulation components and the zeta-potential study confirmed better stability due to the presence of negative charge (-20 to -40 mV). The obtained outcomes for Y1 (29-86 %), Y2 (45-83 %) and Y3 (49-86 %) were analyzed by polynomial equations and the suggested quadratic model were validated. Nebivolol release from SLMs at pH 1.2 and 6.8 was significantly (p < 0.05) affected by lipid concentration. The release mechanism followed Higuchi and zero order models, while n > 0.85 value (Korsmeyer- Peppas) suggested slow erosion along with diffusion. The optimized SLMs have the potential to improve nebivolol oral bioavailability.